Meningkatkan Keputusan Pembelian Yogurt Cheese Works: Dampak Dari Persepsi Harga Dan Kualitas Produk - Meryawan, I Wayan; Kesuma Suryawan, Tjokorda Agung Wijaya; Fitriandari, Mahayanti; Pebriani, Ni Kadek (Akses: Jurnal Penelitian dan Pengabdian Kepada Masyarakat Universitas Ngurah Rai, 2023)
The decision to buy yogurt is based on information about the advantages of the product. The stages of the assessment decision are influenced by some aspects between assumptions or perceptions and product quality. Cheese Works Gianyar Bali as a research location found various problems related to yogurt purchasing decisions. The problem that occurs at Cheese Works Gianyar Bali is shown by the shrinking purchasing decisions for yogurt products. This research concludes that there is a positive and significant effect simultaneously and partially between the perception of price and product quality on the decision to purchase yogurt at Cheese Works Gianyar Bali. The sample of this research is 56 respondents using simple random sampling method. The data analysis used to answer the research objectives are classical assumption testing, multiple linear regression analysis, determination analysis, simultaneous significance testing (F-test), and partial significance testing (t-test). The results of this study found that the simultaneous perception of price and product quality had a significant positive effect on purchasing decisions at Cheese Works Gianyar Bali. Furthermore, partial price perception has a significant positive effect on purchasing decisions at Cheese Works Gianyar Bali and partially product quality has a significant positive effect on purchasing decisions at Cheese Works Gianyar Bali.